Fusion joining of thermoplastic composite wind turbine blades: Lap-shear bond characterization. (September 2019) - Murray, Robynne E.; Roadman, Jason; Beach, Ryan
Abstract: Wind turbine blades are typically manufactured from a small number of components which are bonded together with an adhesive. Over the life span of a wind turbine, the static and fatigue loads in varying environmental conditions can lead to cracking and/or debonding of the adhesive joints, ultimately leading to blade structural collapse. The objective of this work is to investigate fusion joining of wind turbine blades manufactured using thermoplastic resin. Thermoplastic resins for wind turbine blades can reduce cycle times and energy consumption during manufacturing and facilitate end-of-life recycling and on-site manufacturing. Additionally, fusion joining of these materials can replace adhesives, resulting in stronger and more robust blades. This work showed that, compared to typical adhesives used in wind turbine blades, fusion welding resulted in an increase in both the static and fatigue lap-shear strength as compared to bonded thermoplastic composite coupons. This initial coupon-scale research suggests that there is potential for developing fusion welding techniques for full-scale wind turbine blades. Highlights: Thermoplastic composite bonds made with adhesives were compared to resistance- and induction-welded bonds. The fusion-welded thermoplastic composite bonds had higher static and fatigue lap-shear strengths than commonly used wind turbine blade adhesives. Various failure modes were observed for the fusion-welded bonds. Scanning electron microscopy was used to identify improvements in the bonding process to increase bond strengths.